Leserbrief zum Beitrag MRg-HIFU (doi:10.1055/a-0817-5645) - Holger Strunk; Tolga Tonguc; Milka Marinova (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Background The rapid development of information and communication technologies has rendered informatics competencies of healthcare professionals critical in the digital transformation process. Nurses, who constitute a substantial proportion of the healthcare workforce, are expected to develop nursing informatics competencies. These competencies are crucial for effective adaptation to digital healthcare environments and for ensuring the delivery of safe care. Therefore, it is important that informatics competencies are assessed with practical and valid tools. The results of such assessments can provide valuable insights into nurses' educational needs. Objectives This study aimed to evaluate the validity and reliability of the "Nursing Informatics Competency Assessment Tool" (NICAT), originally developed by Rahman (2015), and to adapt it for use in Turkish. Methods Construct validity was examined using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Internal consistency coefficients were calculated to assess reliability. Results EFA revealed a three-factor structure accounting for 71.79% of the total variance. CFA results indicated an acceptable model fit (CFI = 0.925; RMSEA = 0.082). Cronbach's alpha coefficients ranged from 0.764 to 0.968, demonstrating high internal consistency. While the original NICAT study assessed only content validity, this study provides the first empirical testing of its factor structure. Conclusions The 26-item Turkish version of the tool has demonstrated satisfactory validity and reliability. It can be considered a valid, reliable, and practical instrument for assessing nursing informatics competencies. Keywords: Competencies, Medical Informatics, NICAT, Nursing Informatics, Reliability, Validity.